La proporcionalidad de las multas en las infracciones sancionadas con pena privativa de libertad, vulnera principios constitucionales - García Vega, Richard Washington (2015)
This legal research thesis entitled "THE PROPORTION OF FINES IN offenses punishable by imprisonment violates CONSTITUTIONAL PRINCIPLES" discusses methodical and systematic implementation of ancillary multas de way people punished with imprisonment within the principle of proporcionalidad. La research it raises a proposed amendment to Art. 70 Criminal Code of Integral. Introduction as a guide, leads us to analyze the problem in order to find justification inherent reasons where the objectives are formulated and the research hypothesis, which concretariamos, this research. The development of the theoretical framework composes the doctrinal, jurisprudential, legislative and law part compared with three Andean countries that contribute to the research project. The methodology addresses the methods used, the types of research: descriptive, documentary and field. Population, sample and research techniques and instruments described. ...